2003
DOI: 10.1073/pnas.0735876100
|View full text |Cite
|
Sign up to set email alerts
|

Translational control of inducible nitric oxide synthase expression by arginine can explain the arginine paradox

Abstract: L-Arginine is the only endogenous nitrogen-containing substrate of NO synthase (NOS), and it thus governs the production of NO during nervous system development as well as in disease states such as stroke, multiple sclerosis, Parkinson's disease, and HIV dementia. The ''arginine paradox'' refers to the dependence of cellular NO production on exogenous L-arginine concentration despite the theoretical saturation of NOS enzymes with intracellular L-arginine. Herein, we report that decreased availability of L-argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
229
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(243 citation statements)
references
References 41 publications
10
229
3
1
Order By: Relevance
“…NO is produced from the semiessential amino acid L-arginine by two constitutive isoforms of nitric oxide synthase (NOS), endothelial NOS (eNOS, NOS3) and neuronal NOS (nNOS, NOS1). L-arginine is both the substrate and the regulator of NOS (2). The third isoform (iNOS, NOS2) is induced in inflammatory, endothelial, muscle and other cells by a wide range of inflammatory agents, especially cytokines (3), and bacterial endotoxines.…”
Section: Introductionmentioning
confidence: 99%
“…NO is produced from the semiessential amino acid L-arginine by two constitutive isoforms of nitric oxide synthase (NOS), endothelial NOS (eNOS, NOS3) and neuronal NOS (nNOS, NOS1). L-arginine is both the substrate and the regulator of NOS (2). The third isoform (iNOS, NOS2) is induced in inflammatory, endothelial, muscle and other cells by a wide range of inflammatory agents, especially cytokines (3), and bacterial endotoxines.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors have been previously implicated in the suppressive function of MDSCs, including the generation of reactive oxygen species (ROS) and NO by NADPH oxidase 41 and iNOS, 42 the deprivation of extracellular arginine and cysteine by arginase 42 and cysteine transporter X c À , 43 and Fas. 18 The suppressive function of MDSCs seems to be regulated by several transcription factors, including STAT3 and C/EBPb, and several recent studies have shown the STAT3-regulated suppressive functions of MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…24 Briefly, the syngeneic splenocytes were divided into equal numbers and either loaded with 1 lg/ml cytotoxic T lymphocyte (CTL) epitope peptide (human Her-2/neu p63 [TYLPTNASL] peptide or a mixture of E6 [41][42][43][44][45][46][47][48][49][50] [EVYD-FAFRDL] and E7 [49][50][51][52][53][54][55][56][57] [RAHYNIVTF] peptides) or left unpulsed. Peptide-pulsed splenocytes were labeled with chloromethylfluorescein diacetate succinimidyl ester (CFSE; Invitrogen, Carlsbad, CA) at 20 lM, and unpulsed splenocytes were labeled with 2 lM CFSE.…”
Section: In Vivo Cytotoxicity Assaymentioning
confidence: 99%
“…Interestingly, arginine transporters have been held responsible for the 'arginine-paradox', the observation that endothelial NO synthesis can be regulated by varying the extracellular arginine concentration, despite the fact that the reported intracellular arginine concentrations (0.1-1.0 mM) greatly exceed the K m of endothelial nitric oxide synthase (NOS) for arginine (2.9 mM) (Wu & Morris Jr, 1998). Interstingly, Lee et al (2003) recently demonstrated in an in vitro model that arginine concentration upregulates iNOS expression via translational control of iNOS mRNA.…”
Section: Discussionmentioning
confidence: 99%